PERFORMANCE AND CHALLENGES OF CURRENT HOUSEHOLD SOLID WASTE MANAGEMENT SYSTEM IN ABOMEY-CALAVI DISTRICT IN BENIN - CHIDIKOFAN, Djonoumawou Mèmèvègni Grâce Floriane; YATAKPO, Gatienne Léa; KPLE, Melhyas; Nonviho, Guévara; ADJAKPA, Boco Jacques (My University, 2023)
Since 2020, the Beninese government has been experimenting with a new household solid waste management system in five municipalities in southern Benin. The present study aims to assess the performance of this current management system in the central district of Abomey-Calavi. A survey with 236 households and stakeholders, a characterization of solid waste according to household standing and seasons, and SWOT analysis were carried out. The results show that the novelty of the current management system lies in the structuring of the intervention and responsibilities of the various actors. The coordination of the system is the entire responsibility of a new actor, the SGDS (Waste and Sanitation Management Company). At total, 23505 tons of waste are pre-collected in 2022, representing 80% of pre-collection rate. However, the recovery rate is very low. It was concluded that the current solid waste management system is neither optimal nor sustainable again. Public–private–government partnership and collaboration with households deserves to be reinforced. A formalized policy of optimal waste recovery for each component also deserves to be developed. This results can serve as an efficient decision-making tool
Keywords: Household solid waste; Management; Recorvery; SWOT; Performance